2018
DOI: 10.1021/acs.macromol.8b00033
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Behavior of Polymer Droplets: Effects of Droplet Size and Chain Length

Abstract: Monte Carlo computer simulations were utilized to probe the behavior of homopolymer droplets adsorbed at solid surfaces as a function of the number of chains making up the droplets and varying droplet sizes. The wetting behavior is quantified via the ratio of the perpendicular to the parallel component of the effective radii of gyration of the droplets and is analyzed further in terms of the adsorption behavior of the polymer chains and the monomers that constitute the droplets. This analysis is complemented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…If hydrodynamic effects are relevant, the size dependence is [ 6 , 14 ]. Effects due to confinement, for example, of polymer chains lengths in droplets of various sizes have also been studied [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…If hydrodynamic effects are relevant, the size dependence is [ 6 , 14 ]. Effects due to confinement, for example, of polymer chains lengths in droplets of various sizes have also been studied [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the entropically driven wettability can be tailored in a controllable fashion by varying the functionality of polymers. Some other theoretical arguments have also been proposed for predicting the effect of chain length of polymers on wetting/dewetting behaviours . In the work presented here, we attempted to study the effect of chain length on dewetting behaviour of TPPE thin films on silicon surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The wetting property of a polymer droplet is known to be dependent on several factors such as its size, structure, functional groups, etc. 47 The morphologies of polymer thin films thus obtained are reported to vary from continuous films to various discontinuous films including fractals, honeycombs and droplets because of dewetting phenomena. 48,49 Interesting nanostructures such as pancake-like aggregates, zigzag structures and Janus and tripod structures were observed depending on the polymer chain conformations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations